Kinetics and Mechanism of Thermal Decomposition of Malonaldehyde Peroxide (DPM) in Solution - Reguera, Mónica Beatriz (2021)
In this paper, the kinetics of the thermal decomposition reaction of 3,6-diethanal-1,2,4,5 tetroxane (malonaldehydeperoxide, DPM) is investigated in methanol solvents at different temperatures. In the temperature range of 130.0-166.0 ° C studied and at the concentration of 2 x 10-2 M, it follows a first order kinetic law up to at least 60% DPM conversion. The organic products observed were malonaldehyde. A stepwise mechanism of decomposition was proposed where the first step is the homolytic unimolecular rupture of the O-O bond. The activation enthalpy and activation entropy for DPM in methanol were calculated (ΔH0# = 86.1 ± 2.7 kJ mol-1 y ΔS0# = -65.2 ± 6.0 J mol-1 K-1).